Beyond 2D telestration: an evaluation of novel proctoring tools for robot-assisted minimally invasive surgery. Issue 2 (June 2016) - Jarc, Anthony M.; Shah, Swar; Adebar, Troy; Hwang, Eric; Aron, Monish; Gill, Inderbir; Hung, Andrew
Abstract Experienced surgeons commonly mentor trainees as they move through their initial learning curves. During robot-assisted minimally invasive surgery, several tools exist to facilitate proctored cases, such as two-dimensional telestration and a dual surgeon console. The purpose of this study was to evaluate the utility and efficiency of three, novel proctoring tools for robot-assisted minimally invasive surgery, and to compare them to existing proctoring tools. Twenty-six proctor-trainee pairs completed validated, dry-lab training exercises using standard two-dimensional telestration and three, new three-dimensional proctoring tools called ghost tools. During each exercise, proctors mentored trainees by correcting trainee technical errors. Proctors and trainees completed post-study questionnaires to compare the effectiveness of the proctoring tools. Proctors and trainees consistently rated the ghost tools as effective proctoring tools. Both proctors and trainees preferred 3DInstruments and 3DHands over standard two-dimensional telestration (proctorsp  < 0.001 andp  = 0.03, respectively, and traineesp  < 0.001 andp  = 0.002, respectively). In addition, proctors preferred three-dimensional vision of the operative field (used with ghost tools) over two-dimensional vision (p  < 0.001). Total mentoring time and number of instructions provided by the proctor were comparable between all proctoring tools (p  > 0.05). In summary, ghost tools and three-dimensional vision were preferred over standard two-dimensional telestration and two-dimensional vision, respectively, by both proctors and trainees. Proctoring tools—such as ghost tools—have the potential to improve surgeon training by enabling new interactions between a proctor and trainee.